2000
DOI: 10.1042/bj3510313
|View full text |Cite
|
Sign up to set email alerts
|

Impaired reductive regeneration of ascorbic acid in the Goto–Kakizaki diabetic rat

Abstract: Ascorbic acid (AA) is a naturally occurring major antioxidant that is essential for the scavenging of toxic free radicals in both plasma and tissues. AA levels in plasma and tissues have been reported to be significantly lower than normal in diabetic animals and humans, and might contribute to the complications found at the late stages of diabetes. In this study, plasma and hepatic AA levels and AA regeneration were studied in the Goto-Kakizaki diabetic rat (GK rat) to elucidate the mechanism of decreasing pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Plasma and liver AA concentrations are significantly lower in the Goto‐Kakizaki diabetic rat than in controls [42]. NADPH‐dependent regeneration of AA from DHA is also suppressed in the liver of this diabetic rat [42].…”
Section: Diabetesmentioning
confidence: 74%
See 1 more Smart Citation
“…Plasma and liver AA concentrations are significantly lower in the Goto‐Kakizaki diabetic rat than in controls [42]. NADPH‐dependent regeneration of AA from DHA is also suppressed in the liver of this diabetic rat [42].…”
Section: Diabetesmentioning
confidence: 74%
“…Plasma and liver AA concentrations are significantly lower in the Goto‐Kakizaki diabetic rat than in controls [42]. NADPH‐dependent regeneration of AA from DHA is also suppressed in the liver of this diabetic rat [42]. Glucose‐6‐phosphate dehydrogenase activity provides NADPH for DHA reduction and a decrease in the activity of this enzyme in diabetic rat liver may account for the subnormal AA concentrations [43].…”
Section: Diabetesmentioning
confidence: 88%
“…As regards to the other AKR subfamilies, their involvement of diabetes was reported in a few cases. For instance, Northern blot analysis revealed that expression of AKR1C9 (3α‐HSD) was suppressed in the Goto‐Kakizaki diabetic rat liver 37. As shown in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…As regards to the other AKR subfamilies, their involvement of diabetes was reported in a few cases. For instance, Northern blot analysis revealed that expression of AKR1C9 (3a-HSD) was suppressed in the Goto-Kakizaki diabetic rat liver [37]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%